KERJA SAMA SIBER INDONESIA MELALUI BADAN SIBER DAN SANDI NEGARA (BSSN) DI ASIA TENGGARA PADA TAHUN 2018-2020 - Shava Ardra Argiyanti (2023)
The advances in science and technology, and the rapid development of globalization have brought various impacts for the world community, like the threat of cybercrime. Cybercrime can't be felt physically and it is moves in cyberspace, it has become a new threat along with the widespread use of the internet and smartphones. The Southeast Asian region itself is listed as one of the regions with the most internet users in the world, this is also related to the high number of cybercrimes in the Southeast Asian region. Cybercrime that is rife in this region requires the countries within it to cooperate in understanding, solving, and handling with cybercrime itself. Indonesia with the Badan Siber dan Sandi Negara or BSSN must take a role in maintaining regional security stability, especially in cyber field. BSSN has made various efforts in order to maintain national and regional cybersecurity by providing services for cyber incidents, forming a cybersecurity culture, and establishing cooperation with Southeast Asian countries through various forums. With these efforts, BSSN is able to show its contribution in supporting security continuity or stability in the Southeast Asia region itself.